(untitled) (Studia theodisca, 2015)
This article focusses on the trains of thought and motifs that link the aesthetic and ethical foundation of The Man Without Qualities with philosophemes of the Greek antiquity. When Musil states that aesthetics is ethics and that everything is moral, he is drawing on classical ideas that converge in the idealistic notion of unity in diversity. The question of another condition is characteristic of the Romantic tradition that Musil continues (while distancing himself from it), but has a much older heritage, that of the philosophy of antiquity.